Dietary inflammatory potential, genetic susceptibility, and systemic inflammation indices in relation to abdominal aortic aneurysm risk: a prospective cohort study - Wei, Duoliang; Zhong, Yongliang; Liu, Xinyi; Guo, Rutao; Ge, Yipeng; Qiao, Zhiyu; Zhu, Junming (Frontiers in Nutrition, 2025)
BackgroundChronic inflammation and genetic susceptibility are important factors in abdominal aortic aneurysm (AAA) pathogenesis, yet evidence regarding the impact of dietary inflammation on AAA risk remains limited. This study aimed to investigate the association between dietary inflammatory potential, genetic susceptibility, and systemic inflammation in relation to AAA incidence.MethodsIn this prospective cohort study, 142,862 participants from the UK Biobank were followed over an average of 13.8 years. Dietary inflammatory potential was assessed using the Energy-Adjusted Dietary Inflammatory Index (E-DII), while genetic susceptibility was quantified using polygenic risk scores (PRS) derived via PRS-CS methodology. Systemic inflammation indices, including the Systemic Immune-Inflammation Index and the Systemic Inflammation Response Index (SIRI), as well as nutritional and immunological status assessed by the Prognostic Nutritional Index and the Controlling Nutritional Status score, were also examined. In addition, the mediating roles of systemic inflammation indices were evaluated.ResultsHigher E-DII scores were significantly associated with increased AAA risk (HR: 1.36, 95% CI: 1.09–1.71). Individuals with high PRS and high E-DII exhibited a markedly elevated AAA risk compared to those with low PRS and low E-DII (HR: 3.04, 95% CI: 2.21–4.79). SIRI mediated 9.16% (95% CI: 4.81%–17.90%) of the association between dietary inflammation and AAA.ConclusionThis study demonstrates that both dietary inflammatory potential and genetic susceptibility are associated with increased AAA risk, highlighting SIRI as a critical mediator. These findings suggest the potential utility of integrating dietary strategies, genetic screening, and inflammatory biomarkers into targeted AAA prevention programs.